Expression of cytochrome P450 isozyme transcripts and activities in human livers. (3rd April 2021) - Liu, Jie; Lu, Yuan-Fu; Corton, J. Christopher; Klaassen, Curtis D.
Abstract: Individual differences in cytochrome P450 (CYP) enzymes contribute to responses to drugs and environmental chemicals. The expression of CYPs is influenced by sex, age, and ethnicity. Human CYP studies are often conducted with human liver microsomes and liver cells to evaluate chemical induction and drug interactions. However, the basal or constitutive expression of CYP transcripts and enzyme activities in the intact liver are also important in our understanding of individual variation in CYPs. This study utilised 100 human liver samples to profile the constitutive expression of CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6, 2E1, 3A4, and 4A11 enzyme activity and transcript levels. The mRNA expression of the CYPs and xenobiotic receptors AhR, CAR, and PXR was examined via qPCR. Results showed that there was greater inter-individual variation in mRNA expression than in enzyme activities, except for CYP2C19. Females had higher CYP3A4 activity than males. Children had lower CYP4A14 activity, while elderly had lower P450 oxidoreductase activity. Compared to Caucasians, Hispanics had higher CYP2C8 activity and higher CYP2B6, CYP2C9, and CYP2C19 mRNA expression, whereas African Americans had lower CYP2D6 mRNA expression. These results add to our understanding of individual variations in xenobiotic metabolism and toxicology.